Production of Trichophyton rubrum microspores in large quantities and its application to evaluate amorolfine/azole compound interactions in vitro - Laurent, Alexis; Monod, Michel (Mycoses, 2017)
Summary Trichophyton rubrum is the most frequently isolated dermatophyte species in European countries. The lack or poor sporulation of T. rubrum has always been a major complication and a limiting factor when performing antifungal susceptibility testing. Therefore, we describe an in vitro method aiming to enhance sporulation of various T. rubrum isolates in order to perform antifungigrams. A combination of high CO2 tensions and incubation on PDA growth medium revealed to be optimal for sporulation of all tested T. rubrum isolates. This method was further used to examine in vitro the combined effects of amorolfine and azole derivatives against fungal growth using adapted checkerboard microdilution assays and an isobolographic approach of the data, adapted disc diffusion and Etest assays. Non‐antagonistic and synergistic effects were observed in these settings with amorolfine combined to each of the tested azole compounds. The optimised culture method appeared to be suitable for T. rubrum isolates for which antifungigrams were especially difficult to obtain because of the lack of sporulation.